Methodologies in measuring risk of financial statements - Wágner, Vilmos (Acta Agraria Debreceniensis, 2010)
Aim of financial statements’ risk analysis is to optimally allocate the audit resources. That optimum point can be reached, if we achieve maximum possibility of recovery of material risks. There are more than one procedures exist for researching of optimum point or risk assessment in other word, and they are needed to use even parallel. In order to take into consideration effects of risk we need to measure them somehow. At risk assessments risks are usually some kind of result of impact and possibility. Knowledge and measurement of impacts and possibilities are far not enough for assessment of certain risks. In this study I will present a possible usable risk assessment methodology for financial audit activities with using Multi Attribute Utility Theory (MAUT in the followings).